DISEASES CAUSED BY VITAMIN D DEFICIENCY IN CHILDREN. - Alixonova Nilufar (Prospects for innovative technologies in science and education, 2025)
This article analyzes vitamin D deficiency in children and the diseases that arise as a result of it. Vitamin D plays an important role in important biological processes in the body, especially in the development of the bone and muscular system, and in the normalization of calcium and phosphorus metabolism. The work provides detailed information about the physiological significance of vitamin D, the causes of deficiency, clinical symptoms and the most common complication - rickets. Also, methods of prevention and treatment of diseases are considered and scientifically based conclusions are presented on the topic.